Approximate expressions for lightning electromagnetic fields at near and far ranges: Influence of return‐stroke speed. Issue 7 (9th April 2015) - Chen, Yazhou; Wang, Xiaojia; Rakov, Vladimir A.
Abstract The waveforms of lightning return‐stroke electromagnetic fields on ground are studied using the transmission line model. Approximate expressions to calculate lightning electromagnetic fields at near and far ranges are presented. It is found that the waveforms of lightning electric and magnetic fields in the time domain at both near and far ranges can be expressed approximately as the channel‐base current waveform multiplied by a factor which is a function of the return‐stroke speed v and the horizontal distance r between the return‐stroke channel and the observation point on ground. The ranges at which the approximate expressions are valid are determined. The ranges of validity increase with increasing the return‐stroke speed, and the near and far field approximate expressions converge to the exact formula as the return‐stroke speed approaches the speed of light.